Network Architectures, Management, and Applications IX 2011
DOI: 10.1117/12.904215
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic routing and frequency slot allocation in elastic optical path network using adaptive modulations with consideration of both spectrum availability and distance

Abstract: We proposed a dynamic routing and frequency slots allocation scheme which adopted the adaptive modulation for a novel Spectrum-sLICed Elastic optical path network (SLICE). In our dynamic routing scheme, both spectrum resource availability (SRA) and distance (hop number) are considered at the modulation format selection phase for adaptive modulation. We then conducted numerical simulation to compare our Spectrum Resource Adaptive and Distance Adaptive (SRA-DA) mechanism with previous DA in both small network to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These RSA schemes allow a demand to be split into multiple demands and transmitted on multiple paths. Thus, multipath-routing-based RSA/RMSA schemes [21,22] can dramatically reduce the blocking probability of traffic demands compared with single-path-routing-based RSA/RMSA schemes [17][18][19][20]. However, for multipath routing, the differential delay between routing paths will lead to increased cost of network devices and network maintenance.…”
Section: Related Work and Our Contributionsmentioning
confidence: 94%
See 3 more Smart Citations
“…These RSA schemes allow a demand to be split into multiple demands and transmitted on multiple paths. Thus, multipath-routing-based RSA/RMSA schemes [21,22] can dramatically reduce the blocking probability of traffic demands compared with single-path-routing-based RSA/RMSA schemes [17][18][19][20]. However, for multipath routing, the differential delay between routing paths will lead to increased cost of network devices and network maintenance.…”
Section: Related Work and Our Contributionsmentioning
confidence: 94%
“…However, the performance of MSP is unsatisfactory, and the computational complexity of SPV is very high. In addition, the studies reported in [17][18][19][20] assume that the traffic demands may have arbitrary bandwidth requirement, and the proposed algorithms are not appropriate for EONs with mixed regular line rates (e.g., 40∕100∕400 Gb∕s).…”
Section: Related Work and Our Contributionsmentioning
confidence: 97%
See 2 more Smart Citations
“…Their efficient heuristic algorithms based on spectrum window planes were proposed for implementing distance and modulation format-adaptive RSA, so as to maximize spare capacity sharing among multiple protection paths. The authors of [15] proposed two dynamic RSA algorithms based on K shortest path (KSP); the algorithm needs to determine the candidate path in advance. In [16], the improved shortest path (MSP) algorithm and the spectrum constrained path vector search (SVP) algorithm were addressed, which can further improve network performance.…”
Section: Related Workmentioning
confidence: 99%